2021
DOI: 10.1542/peds.2020-044685
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Among Infants <90 Days of Age Admitted for Serious Bacterial Infection Evaluation

Abstract: This is a prepublication version of an article that has undergone peer review and been accepted for publication but is not the final version of record. This paper may be cited using the DOI and date of access. This paper may contain information that has errors in facts, figures, and statements, and will be corrected in the final published version. The journal is providing an early version of this article to expedite access to this information. The American Academy of Pediatrics, the editors, and authors are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 35 publications
9
20
0
Order By: Relevance
“…It is thought that the difference in severity from SARS-CoV-2 infection between age groups relates to distinct immune responses and expression in receptors of angiotensin-converting enzyme-2 (ACE-2) in younger children [ 30 ]. However, consistent with previous studies, we found that amongst infants, neonates aged <1 month were at increased risk for hospitalization [ 9 , 10 , 13 , 15 , 31 ]. Although a low threshold for admission in infants aged less than 6 to 12 weeks who present with fever may impact hospitalization rates, a larger proportion of neonates aged <1 month admitted for COVID-19 have also required respiratory support compared to older infants, including 5 who required mechanical ventilation [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…It is thought that the difference in severity from SARS-CoV-2 infection between age groups relates to distinct immune responses and expression in receptors of angiotensin-converting enzyme-2 (ACE-2) in younger children [ 30 ]. However, consistent with previous studies, we found that amongst infants, neonates aged <1 month were at increased risk for hospitalization [ 9 , 10 , 13 , 15 , 31 ]. Although a low threshold for admission in infants aged less than 6 to 12 weeks who present with fever may impact hospitalization rates, a larger proportion of neonates aged <1 month admitted for COVID-19 have also required respiratory support compared to older infants, including 5 who required mechanical ventilation [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…The implications of coinfection with viruses and atypical bacteria on clinical features, laboratory and radiological examinations, treatments and outcomes are still unclear ( 58 ). Given that young children have the highest frequency of coinfections (notably with RSV and PIV or ADV), one must anticipate a future increment of coinfections with common respiratory viruses and SARS-CoV-2 ( 11 , 59 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been suggested that infants should be tested for COVID-19, especially in periods when there is a history of exposure and the number of cases is high [ 8 , 12–15 ]. The most common complaints in COVID-19 (+) infants are fever, cough, vomiting, rhinorrhea, irritability and nasal congestion [ 16–18 ]. To our knowledge, no study has compared COVID-19-positive and -negative patients in febrile infants evaluated as FWS.…”
Section: Discussionmentioning
confidence: 99%